(untitled) - Rose, Peter S (Boston, 2008)
This book gives us a lot of useful and relevant information about what business and service is going on in the commerical banks(most are in US) everyday. English is plain and easy to understand. Maths is not much and at introductory level (which is enough for finacial service i suppose). If you are also new to bank industry, this book can be the first one for your learning
Keywords: Financial institutions,Bank management,Banks and banking, International,Thể chế tài chính ngân hàng; United States,United States,Hoa Kỳ